Pengaruh Pemberian Ekstrak Kecambah Kacang Hijau (Phaseolus Radiatus L.) Terhadap Kadar Katalase Pada Tikus Jantan Galur Wistar Yang Diinduksi Herbisida Paraquat - Sundawa, Angga Pria; Trisnasdi, Reza Adityas; Hikmah, Annisa Nurul (Jurnal Biomedika dan Kesehatan, 2024)
Background Exposure to herbicide paraquat affects the body's organs of antioxidants that can exceed the capacity of antioxidant enzymes in the human body which causes the production of Reactive Oxygen Species (ROS). cause oxidative stress. This causes the endogenous antioxidants to decrease so prevention requires exogenous antioxidants such as mung bean sprout supplements. The effect of mung bean sprouts can reduce oxidative stress caused by the herbicide paraquat. This study aimed to determine the effect of mung bean sprout extract on catalase levels in male Wistar rats induced with paraquat herbicide. Methods This research is experimental with a posttest-only controlled Group Design. The research subjects were 25 male Wistar rats randomly divided into 5 groups, namely K1, K2, K3, K4, and K5. Groups K3, K4, and K5 were given a green bean sprout extract supplement at 21.6 mg/200 g BW/day, 43.2 mg/200 g BW/day, and 86.4 mg/200 g BW/day. 16 blood samples were taken for examination of catalase levels. Data were analyzed using the Kruskal-Wallis test. Results The mean catalase level was highest in the K1 group compared to the K3, K4, and K5 groups. The results of the Kruskal-Wallis test on catalase levels showed a significant difference between groups (p=0.000). Conclusions Supplementing green bean sprout extract with doses of 21.6 mg/200 g BW/day, 43.2 mg/200 g BW/day and 86.4 mg/200 g BW/day could increase catalase levels in male Wistar rats induced by paraquat herbicide.